Evaluation of the Efficacy of Transdermal Administration of Maropitant in Managing Vomiting in Cats - Youcef Boukaache; Marie-Laurence Ferret; Valerie Delteil-Prevotat; Karim Khoukh; Andra Enache; Dorothee Iwaszkiw; Sebastien Bertin; Fabien Bruno (Open Veterinary Journal, 2022)
Background. Antiemetic maropitant is a widely used medication for treating acute and chronic vomiting in cats. It is available as tablets or injectable solution (Cerenia®). The oral and injectable routes being especially difficult to pursue in cats experiencing vomiting and nausea, the transdermal administration might be an efficient alternative. The hypothesis of this study was that transdermal maropitant would achieve therapeutic serum concentrations with minimal short-term adverse effects.